MANAGEMENT BANDWIDTH MENGGUNAKAN HIERARCHICAL TOKEN BUCKET PADA PT. DUTAFLOW HIDROLIK - Dede Sopyan Novalga (TECHSI - Jurnal Teknik Informatika, 2021)
Dede Sopyan Novalga (12171058), Bandwidth Management Using HierarchicalToken Bucket at PT. Dutaflow HidrolikThe use of the internet in a company with a large number of users and usedsimultaneously is very important to control internet network traffic. Therefore, it isnecessary to adjust the bandwidth adjustment so that there is no injustice inaccessing an internet network, both LAN and wireless networks. The application ofthis bandwidth management method is very appropriate for managing bandwidth oneach computer. The method used to manage bandwidth is to use the token buckethierarchy method. With Mikrotik router and winbox tools, it is very easy to set andmanage bandwidth on each client computer. In the winbox tool, you can set thedesired bandwidth distribution. However, the maximum bandwidth limit cannotexceed the maximum limit provided by the internet network provider. Afterimplementing bandwidth management using the token bucket hierarchy, thebandwidth distribution on each client computer can be adjusted as needed. And itwon't happen again that one client can get more bandwidth while another client getsless bandwidth. So it can be concluded that the application of this method is veryeffective. Besides, it must be assisted with supporting hardware and software.Keywords: Bandwidth Management, Hierarchical Token Bucket